2013
DOI: 10.1007/s00122-013-2198-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between line per se and testcross performance for eight agronomic and quality traits in winter rye

Abstract: We investigated associations between line per se and testcross performance in rye and suggested that selection for per se performance is valuable for several traits in multi-stage selection programs. Genotypic correlation between line per se and testcross performance is an important quantitative-genetic parameter for optimizing hybrid breeding programs. The main goal of this survey was to study the association of line per se and testcross performance at the phenotypic level. We used experimental data from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 12 publications
2
8
0
1
Order By: Relevance
“…We observed that testcrosses had relatively reduced genetic variance compared with inbred lines. This is in accordance with the quantitative genetic theory where the genetic coefficient of variation is expected to be about four times more in inbred lines than that of testcrosses (Miedaner et al, 2014;Smith, 1986). The reduced genetic variation is attributable to the fact that all inbred lines were crossed to one tester.…”
Section: Reduced Genetic Variation For Grain Yield Under Low P In Tessupporting
confidence: 89%
See 1 more Smart Citation
“…We observed that testcrosses had relatively reduced genetic variance compared with inbred lines. This is in accordance with the quantitative genetic theory where the genetic coefficient of variation is expected to be about four times more in inbred lines than that of testcrosses (Miedaner et al, 2014;Smith, 1986). The reduced genetic variation is attributable to the fact that all inbred lines were crossed to one tester.…”
Section: Reduced Genetic Variation For Grain Yield Under Low P In Tessupporting
confidence: 89%
“…This is in accordance with the quantitative genetic theory where the genetic coefficient of variation is expected to be about four times more in inbred lines than that of testcrosses (Miedaner et al, 2014;Smith, 1986). This is in accordance with the quantitative genetic theory where the genetic coefficient of variation is expected to be about four times more in inbred lines than that of testcrosses (Miedaner et al, 2014;Smith, 1986).…”
Section: Reduced Genetic Variation For Grain Yield Under Low P In Tessupporting
confidence: 89%
“…Замечено, что по мере усложнения структуры признака генотипические корреляции (r g ) становятся слабее. Самые высокие корреляции (r g  0,7) авторы выявили для высоты растения, массы 1000 зерен, а также числа падения и содержания крахмала (24). По нашим данным (табл.…”
Section: эффекты общей и специфической комбинационно способности (оксunclassified
“…Therefore, to compensate for poor germination of aerially seeded crops, seeding rates may need to be increased, which would subsequently increase input costs. However, both camelina and pennycress have very small seeds compared to, for example, winter rye (about 0.8, 0.8, and 33 g 1000 À1 seeds, respectively), which would serve to lower aerial seeding costs on a unit-area basis (Robinson, 1987;Phippen et al, 2010;Miedaner et al, 2014).…”
Section: Agronomicmentioning
confidence: 99%